2020
DOI: 10.1590/1806-9061-2020-1258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bile Acids and Lipase Supplementation in Low-Energy Diets on Growth Performance, Fat Digestibility and Meat Quality in Broiler Chickens

Abstract: The aim of this study was to investigate the effect of bile acids and lipase supplementation in low energy (LE) diets on growth, fat digestibility, serum lipid profile and meat quality of broilers. Seven hundred one-day-old broiler chicks were divided into 5 dietary treatments with five replicates of 28 birds each. The five treatments were: i) high energy diet (HE; metabolizable energy (ME) = 3,000 and 3,170 kcal/kg for starter and finisher diet), ii) low energy diet (LE; ME = 2,900 and 3,070 kcal/kg for start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…To analyze fermentation characteristics of silages, 20 g wet samples were taken and homogenized in 180 mL sterile water at 4°C for 24 h ( Arshad et al, 2020 ). The mixture was then filtered through rapid qualitative filter paper (Fushun Civil Affairs Filter Paper Factory, Liaoning, China) and centrifuged at 3000 r/min for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…To analyze fermentation characteristics of silages, 20 g wet samples were taken and homogenized in 180 mL sterile water at 4°C for 24 h ( Arshad et al, 2020 ). The mixture was then filtered through rapid qualitative filter paper (Fushun Civil Affairs Filter Paper Factory, Liaoning, China) and centrifuged at 3000 r/min for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Feeding and management: Birds were fed on the standard feed as described in the literature (Hussain et al, 2018;Xu et al, 2019;Arshad et al, 2020;Bajwa et al, 2020;Kamran et al, 2020;Shahid et al, 2020;Shahid et al, 2021). Birds were managed according to standard procedure as described in literature (Hussain et al, 2018;Xu et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Increased pH could lead to increased WHC in breast meat [ 115 ]. However, Arshad et al [ 116 ] showed that low-energy diets (−100 kcal/kg in the starter feed and finisher feed) did not modulate pH, WHC, or lightness in the breast meat.…”
Section: Effects Of Nutritional Interventions On the Meat Quality Of ...mentioning
confidence: 99%